PENERAPAN MODEL PROBLEM BASED LEARNING (PBL) BERBASIS KONTEKS PEMBENTUKAN LAHAN SAWAH BERBENTUK SEGITIGA PADA MATERI TEOREMA PYTHAGORAS UNTUK MENINGKATKAN KEMAMPUAN BERPIKIR KRITIS SISWA SMP - Febilawati, Anggraeni; Abi Suwito; Frenza Fairuz Firmansyah (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aimed to determine the effect of the Problem Based Learning (PBL) model on junior high school students’ critical thinking skills. The study employed a quantitative approach using a quasi-experimental method with a Nonequivalent Control Group Design. The research sample consisted of two classes, namely an experimental class taught using the Problem Based Learning (PBL) model and a control class taught using conventional learning methods. Data were collected through critical thinking skill tests in the form of pretests and posttests. The data were analyzed using descriptive statistics, N-Gain tests, and effect size tests. The results showed that the average pretest score of students was 71.5094 and increased to 81.8868 in the posttest after the implementation of the Problem Based Learning (PBL) model. The N-Gain test result obtained an average score of 0.2320, which was categorized as low. In addition, the effect size test showed a Cohen’s d value of 0.104, which was included in the small category. The findings indicate that the implementation of the Problem Based Learning (PBL) model was able to improve students’ critical thinking skills, although the improvement was still relatively low. The Problem Based Learning (PBL) model helped students become more active in analyzing problems, participating in discussions, and finding solutions during the learning process. Therefore, the Problem Based Learning (PBL) model can be used as an alternative learning model to support the development of junior high school students’ critical thinking skills.